The Effectiveness of the Discovery Learning Model in Improving Students' Critical Thinking Skills in Fiqh Learning at MTs Raudlatul Ulum Guyangan Trangkil Pati - Najwa (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to explore the effectiveness of the Discovery Learning learning model in improving students' critical thinking skills in the Fiqh subject at MTs Raudlatul Ulum Guyangan Trangkil Pati. The research method used is classroom action research with two implementation cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through pre- and post-tests, classroom observations, and interviews with teachers and students. The results of the study indicate that the application of the Discovery Learning learning model can improve students' critical thinking skills. In the first cycle, students showed an increase in participating in group discussions and were able to analyze Fiqh concepts, although some students still had difficulty with the open-ended tasks given. In the second cycle, with the use of more varied multimedia media and more structured assignments, students were more active in participating and were able to analyze and apply Fiqh principles in real-life situations better. Based on the results of the study, it can be concluded that the Discovery Learning model is effective in improving students' critical thinking skills in the Fiqh subject, and makes a positive contribution to the development of high-level thinking skills that can be applied in everyday life.